Approaches to Ergativity in Indo-Aryan - Stroński, Krzysztof (Lingua Posnaniensis, 2010)
The present paper aims at giving an overview of the basic theories pertaining to the emergence and development of ergativity in Indo-Aryan. It has usually been argued that ergativity could have been derived either from the passive or the originally PIE ergative construction. In addition to these two basic approaches to ergativity in IA, other perspectives are also taken into consideration here, namely the theory which is based on the pragmatic properties of OIA, and the hypothesis of the possible borrowing from the substratum languages. The existing models of the historical scenarios of the emergence of ergativity in IA, including their later mutations, are confronted with the hypothesis of the possible active typology of PIE. The active residues in OIA and its continuants might prove that ergativity arose due to the transition from the PIE active to the nominative stage attested in the daughter languages.